Implementation of Qanun Aceh Number 11 of 2018 concerning Islamic Financial Institutions in Increasing Financing for Micro Enterprises in Aceh - Putri Balqis Vilza; Yusri Yusri; Muhammad Gaussyah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Islamic Financial Institutions play a vital role in strengthening the Islamic economy in Aceh, particularly through financing micro businesses. Article 14 of Qanun Aceh Number 11 of 2018 sets a target of 40% profit-sharing-based financing for Micro, Small, and Medium Enterprises (MSMEs) by 2024. However, the realization of financing with profit-sharing contracts is still low. This study aims to examine the implementation of Qanun Number 11 of 2018 in facilitating micro business financing in Aceh, identify obstacles in its implementation, and analyze the roles of the government, society, and the private sector in supporting this process. The study uses an empirical juridical method, collecting data through literature studies, interviews, and observations. Data analysis is conducted qualitatively with a prescriptive analytical approach. Challenges to financing distribution include business actors not meeting credit quality assessments and prudential banking standards, causing banks to implement risk management strategies to prevent non-performing loans. Additionally, low financial literacy among business actors remains a significant barrier. The local government supports micro business financing by establishing the Technical Implementation Unit of the Integrated Business Service Office, providing financial assistance, and introducing the draft Qanun of Aceh Sharia Financing Guarantee. Bank Aceh Syariah offers training and coaching for MSMEs, while Bank Syariah Indonesia aids MSMEs through the MSME Center and the Muslim Entrepreneur program. Improving financial literacy is essential for business development. The study recommends that the Aceh Government strengthen the implementation of Qanun Sharia Financial Institutions, increase profit-sharing-based MSME financing, and promote financial literacy.